THE INFLUENCE OF TEACHERS’ SELF-EFFICACY AND MOTIVATION ON THE 2024 NATIONAL CURRICULUM IMPLEMENTATION - Isna, Nuzulul; Asdarina, Orin; Nurhaliza, Khairul (Lembaga Penelitian dan Pengabdian (LP2M) STKIP Bina Bangsa Getsempena, 2025)
The purpose of this study was to find the relationship between teacher self-efficacy and teacher motivation towards the implementation of the 2024 National Curriculum in Indonesia. The study used quantitative descriptive. The sample in this study were teachers who teach at various school levels from various districts in Aceh Province. The data collection process was carried out on 226 data sets which were analyzed by correlation analysis using SPSS. Qualitative information was analyzed through content analysis using Nvivo 12 to support quantitative information. Based on the results of the data analysis, it was revealed that there was a moderate correlation between teacher self-efficacy and self-motivation. However, teacher self-efficacy and motivation did not have any influence on teacher implementation of the 2024 National Curriculum. In addition, the factors that influence the implementation of the new curriculum and the challenges faced are also further disclosed.